Studi Fenomenologi Pengalaman Ibu dalam Merawat Anak Stunting Usia 6 – 24 Bulan Berbasis Health Belief Model - Fathmy Fitriany Soulissa; Yuni Sufyanti Arief; Ririn Probowati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the phenomenological description of the experiences of mothers caring for children with stunting at the age of 6-24 months. The method used is qualitative with a phenomenological study design in mothers who care for children with stunting aged 6-24 months, with 15 participants selected by purposive sampling. The results showed that there were four main themes related to the experience of mothers caring for children with stunting aged 6-24 months, namely exclusive breastfeeding, the inappropriateness of MP-ASI giving, lack of mother's knowledge and non-fluent breastfeeding. In conclusion, the mother's experience in caring for stunted children, namely exclusive breastfeeding is incomplete, breastfeeding is replaced by Sufor, early MP-ASI giving, inappropriateness in giving MP-ASI, lack of knowledge of mothers about child growth, child nutrition and the importance of exclusive breastfeeding and non-current breastfeeding caused by heredity and only a little out. Keywords: Children, Health Belief Model, Mother, Behavior, Stunting